1979
DOI: 10.1677/joe.0.0800315
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Function Tests in Dogs With Hyperfunctioning Adrenocortical Tumours

Abstract: The response has been studied in nine dogs with hyperadrenocorticism due to adrenocortical tumours to the administration of dexamethasone, insulin, lysine-vasopressin and tetracosactide by measuring the changes in plasma cortisol concentration. Administration of dexamethasone did not produce a decrease in the plasma concentration of cortisol in any of these dogs. Administration of insulin caused slight increases in the plasma concentration of cortisol in four out of eight dogs. Lysine-vasopressin increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…For 14 dogs with hyperadrenocorticism as diag nosed by pituitary-adrenocortical function tests [17,18] permission was obtained for autopsy and subsequent investigations. 8 dogs had PDH and 6 dogs had an adrenocortical tumor.…”
Section: Animalsmentioning
confidence: 99%
“…For 14 dogs with hyperadrenocorticism as diag nosed by pituitary-adrenocortical function tests [17,18] permission was obtained for autopsy and subsequent investigations. 8 dogs had PDH and 6 dogs had an adrenocortical tumor.…”
Section: Animalsmentioning
confidence: 99%
“…The adrenal function of cat 1 was hardly be suppressed by high doses of dexamethasone and was slightly stimulated by synthetic ACTH in comparison with data for healty cats (24). This suggests an autonomous hyperadrenocorticism, which is indicative of the presence of an adrenal tumour (12,13,17). However other studies have demonstrated that dexamethasone resistance, as found in this cat, can also be caused by a dysfunctioning pituitary gland (2,21).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are indicative of an adrenal tumour (12,13), and therefore a laparotomy was performed. However no abnormalities of the adrenal glands were observed.…”
Section: Clinical Data Catmentioning
confidence: 99%
“…Peaks of normal dogs' cortisol levels overlap with those of hyperadrenocorticoid dogs and at least 50% of hyperadrenocorticoid dogs have resting cortisol concentrations in the normal range(2)(4)(5)(22)(4n)(47 (48). Stress, such as hospitalisation, handling, blood sampling and other factors, can also result in normocorticoid dogs having elevated basal cortisol levels(l )(4) (38).…”
Section: Resting Plasma Cortisolmentioning
confidence: 99%